Pharmacokinetic Analysis of Diosgenin in Rat Plasma by a UPLC-MS/MS Approach. (30th September 2022) - Liu, Pei; Xu, Lin; Guo, Jing-han; Chang, Jin-hua; Liu, Xi-gang; Xue, He-fei; Wang, Ru-xing; Li, Zhong-si; Miao, Guang-xin; Liu, Cui-zhe; Zhou, Jian-yu
Abstract : Diosgenin, a steroidal sapogenin, has attracted attention worldwide owing to its pharmacological properties, including antitumor, cardiovascular protective, hypolipidemic, and anti-inflammatory effects. The current diosgenin analysis methods have the disadvantages of long analysis time and low sensitivity. The aim of the present study was to establish an efficient, sensitive ultrahigh-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) approach for pharmacokinetic analysis of diosgenin amorphous solid dispersion (ASD) using tanshinone IIA as an internal standard (IS). Male Sprague-Dawley rats were orally administered diosgenin ASD, and orbital blood samples were collected for analysis. Protein precipitation was performed with methanol-acetonitrile (50 : 50, v/v), and the analytes were separated under isocratic elution by applying acetonitrile and 0.03% formic acid aqueous solution at a ratio of 80 : 20 as the mobile phase. MS with positive electron spray ionization in multiple reaction monitoring modes was applied to determine diosgenin and IS with m/z 415.2⟶271.2 and m/z 295.2⟶277.1, respectively. This approach showed a low limit of quantification of 0.5 ng/ml for diosgenin and could detect this molecule at a concentration range of 0.5 to 1, 500 ng/ml ( r = 0.99725). The approach was found to have intra- and inter-day precision values ranging from 1.42% to 6.91% and from 1.25% to 3.68%, respectively. Additionally, the method showed an accuracy of -6.54 to 4.71%. The recoveries of diosgenin and tanshinone IIA were 85.81–100.27% and 98.29%, respectively, with negligible matrix effects. Diosgenin and IS were stable under multiple storage conditions. Pharmacokinetic analysis showed that the C max and AUC0⟶t of diosgenin ASD were significantly higher than those of the bulk drug. A sensitive, simple, UPLC-MS/MS analysis approach was established and used for the pharmacokinetic analysis of diosgenin ASD in rats after oral administration.